Dynamic actin/septin network in megakaryocytes coordinates proplatelet elaboration - Isabelle C. Becker; Adrian R. Wilkie; Bret A. Unger; Anthony R. Sciaudone; Farheen Fatima; I-Ting Tsai; Ke Xu; Kellie R. Machlus; Joseph E. Italiano (Haematologica, 2023)
Megakaryocytes (MK) undergo extensive cytoskeletal rearrangements as they give rise to platelets. While cortical microtubule sliding has been implicated in proplatelet formation, the role of the actin cytoskeleton in proplatelet elongation is less understood. It is assumed that actin filament reorganization is important for platelet generation given that mouse models with mutations in actin-associated proteins exhibit thrombocytopenia. However, due to the essential role of the actin network during MK development, a differential understanding of the contribution of the actin cytoskeleton on proplatelet release is lacking. Here, we reveal that inhibition of actin polymerization impairs the formation of elaborate proplatelets by hampering proplatelet extension and bead formation along the proplatelet shaft, which was mostly independent of changes in cortical microtubule sliding. We identify Cdc42 and its downstream effectors, septins, as critical regulators of intracellular actin dynamics in MK, inhibition of which, similarly to inhibition of actin polymerization, impairs proplatelet movement and beading. Super-resolution microscopy revealed a differential association of distinctive septins with the actin and microtubule cytoskeleton, respectively, which was disrupted upon septin inhibition and diminished intracellular filamentous actin dynamics. In vivo, septins, similarly to F-actin, were subject to changes in expression upon enforcing proplatelet formation through prior platelet depletion. In summary, we demonstrate that a Cdc42/septin axis is not only important for MK maturation and polarization, but is further required for intracellular actin dynamics during proplatelet formation.